Congenital heart surgery and acute kidney injury. Issue 1 (February 2017) - Webb, Tennille N.; Goldstein, Stuart L.
Abstract : Purpose of review: The incidence of cardiac surgery-associated acute kidney injury (CS-AKI) continues to increase and is associated with significant morbidity and mortality. Early diagnosis and identification of patients at risk are extremely important. Therefore, identifying associated risk factors, biomarkers for earlier detection, prevention and therapeutic options for CS-AKI warrant special attention. Recent findings: The current diagnosis of acute kidney injury (AKI) largely depends upon the functional biomarkers serum creatinine and oliguria leading to delays in diagnosis and worsening outcomes. Novel biomarkers are now being investigated to aid in providing an earlier AKI diagnosis as well as predicting its severity. Combining functional and tubular biomarkers have proven to provide even better prediction of AKI development and severity. Due to the limited therapeutic options available for CS-AKI, it is imperative to identify those patients at risk early to help mitigate worsening or severe AKI; hence, combining biomarkers should be beneficial. Summary: It is extremely important to identify those who are at increased risk for CS-AKI with the foremost goal being that of prevention to help decrease morbidity and mortality. Combining functional and tubular biomarkers can assist with early identification. Once identified, early interventions including avoidance of nephrotoxins, decreasing cardiopulmonary bypass time, avoiding fluid overload and early initiation of renal replacement therapy may lead to improved clinical outcomes.